Correction to: GPR68 deletion impairs hippocampal long-term potentiation and passive avoidance behavior - Yuanyuan Xu; Mike T. Lin; Xiang-ming Zha (Molecular Brain, 2021)
An amendment to this paper has been published and can be accessed via the original article.